Sudden Unexpected Death in Epileptic Patient Case Report - Özer, Erdal; Yurtman, Talat; Bütün, Celal (The Bulletin of Legal Medicine, 2006)
The probability of sudden death for patient with epilepsy is almost 24 times higher than for someone without epilepsy. Our case was a 40 years old woman with epilepsy who was six months pregnant when she was dead at her home. Although external examination and autopsy were performed, no pathological signs indicating a cause for death or no signs of trauma indicating an epileptic seizure were observed. Nothing was found in toxicological analysis to reveal a reason for death. When external examination, autopsy report, scene investigation and medical history in forensic investigation folder are evaluated together, reason of death is thought to be definete sudden unexpected death in epileptic patient according to SU-DEP criteria. This case is presented to attract attention to autopsies of patients with epilepsy and to discuss the principles of medicolegal approach to these cases. Key words: Epilepsy, sudden death, SUDEP, pregnancy